(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The company’s consumption of its shares considered as an exceptional procedure, which fundamentally different from its purposes , it is the result of reconciling the necessities of practical reality on the one hand and the right of the shareholder to stay and continue in the company on the other hand, and despite the importance of this process, but its legal organization did not receive the attention required Whether in terms of its complexity, complex effects or the precise questions it raises regarding the nature of the shares that are given to the shareholder whose shares were consumed, and the relationship of the stock consumption to the capital of the company. Which makes its study and research in its concept on the one hand and the mechanism of implementation and effects on the other hand is very important because of its role in removing the ambiguity, and thus prevent the transformation into a fraudulent tool. تعدُ عملية استهلاك الشركة لأسهمها من الإجراءات الاستثنائية الخارجة من حيث المبدأ عن أغراض الشركة الأساسية، فهي وليدة التوفيق بين ضرورات الواقع العمليّ من جهة وحق المساهم في البقاء والاستمرار في الشركة من جهة ثانية. وعلى الرغم من أهمية هذه العملية إلا أن تنظيمها القانوني لم يحظى بالاهتمام المطلوب سواء لجهة ضبط ماهيتها وأثارها، أو لجهة الأسئلة الدقيقة التي تطرحها والمتعلقة بالأسهم التي تمنح للمساهم الذي استهلكت أسهمه والمسماة أسهم تمتع، وعلاقة استهلاك الأسهم برأس مال الشركة، الأمر الذي يجعل من دراستها والبحث في مفهومها وآلية تنفيذها وآثارها أمراً غاية في الأهمية، لما له من دور في إزالة ما يعتريها من غموض، وبالتالي الحيلولة دون تحولها إلى أداة احتيالية.